Landasan dan Paradigma Pengembangan Kurikulum Pendidikan Agama Islam (PAI) - Reni Marvianasari; Agus Zaenul Fitri; Abd. Aziz (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
National education is education based on Pancasila and laws that are rooted in the religious and cultural values ​​of the Indonesian nation. Over time there have been significant changes in the world of Islamic religious education so that the process requires a series of appropriate curriculum development with a strong foundation so that the direction of the development goals is clear, therefore the right foundation is needed to be applied in developing the Islamic religious education curriculum. These foundations include philosophical, psychological, socio-cultural, scientific and technological foundations. Islamic religious education is directed at forming faith and devotion, having knowledge and skills, being able to develop creativity and responsibility, being able to develop high intelligence with noble character and love for the nation and fellow human beings. To achieve what is expected, the curriculum has a very urgent position as a guideline for determining the direction of educational content and objectives. Therefore, curriculum development in the field of Islamic Religious Education is part of the educational strategy in forming students with Rahmatan Lil Alamin character.